Definition of psoriasis severity in routine clinical care: current guidelines fail to capture the complexity of long‐term psoriasis management. (1st December 2018) - Augustin, M.; Langenbruch, A.; Gutknecht, M.; Reich, K.; Körber, A.; Maaßen, D.; Mrowietz, U.; Thaçi, D.; von Kiedrowski, R.; Radtke, M.A.
Summary: Background: Assessment of disease severity is an essential component of psoriasis management. Moderate‐to‐severe disease qualifies for systemic treatment but different definitions are used. Objectives: To analyse the impact of different severity definitions for psoriasis in real‐world healthcare. Methods: Cross‐sectional data on 3274 patients with psoriasis from more than 200 dermatology offices and clinics across Germany were analysed for disease severity based on Psoriasis Area and Severity Index (PASI) and Dermatology Life Quality Index (DLQI). The proportions of patients having moderate‐to‐severe disease were determined accordingly. Results: The proportion of patients meeting the European consensus criteria for moderate‐to‐severe psoriasis (PASI AND DLQI > 10) was 14·0%, although 45·3% attained at least PASI OR DLQI > 10. Consideration of all patients on systemic drugs as being 'moderate‐to‐severe' increased these proportions to 56·9% and 75·2%, respectively. When only PASI > 10 was used, moderate‐to‐severe disease affected 35·3% and 69·3%, respectively. Conclusions: The proportion of patients with psoriasis under dermatological care considered to have moderate‐to‐severe disease varies considerably according to how the latter is defined, resulting in uncertainty and inequity of access to systemic therapy. We propose an international standardisation in this for the sake of more reliable treatment and healthcare planning.